Developing a measure of work uncertainty. Issue 1 (27th November 2012) - Leach, Desmond; Hagger‐Johnson, Gareth; Doerner, Nadin; Wall, Toby; Turner, Nick; Dawson, Jeremy; Grote, Gudela
<x xml:space="preserve">Abstract</x> Uncertainty is a key contingency in the relationship between work characteristics and outcomes such as employee performance and well‐being. In this paper, we specify and test a self‐report measure of work uncertainty for use in any setting to facilitate research and decision making regarding the design of work. Using data collected from three diverse samples, analyses found support for a multi‐dimensional model that corresponds to resource, task, and input/output sources of uncertainty. The scales showed discriminant validity, and task uncertainty was found to moderate the relationship between job control and intrinsic job satisfaction in a form consistent with theoretical predictions. Practitioner Points The self‐report measure of work uncertainty may be used to evaluate existing work design and facilitate its redesign. As research demonstrates, it is critical that the level of job control afforded to employees is congruent with the level of uncertainty they experience. Failure to consider the role of uncertainty in linking job control to outcomes (e.g., performance, well‐being) can undermine work redesign investment.